Edukasi Makanan Jajanan Sehat, Halal dan Thoyib sebagai Upaya Pencegahan Penyakit Diabetes Melitus Usia Dini di Lingkungan Sekolah Dasar Inpres Parang Kelurahan Lanna Parangloe Gowa - Fatmah Afrianty Gobel; Asrini Safitri; Sumiaty Sumiaty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
SD Inpres Parang, located in Kelurahan Lanna, Kecamatan Parangloe, Kabupaten Gowa, educates 244 students. Observations revealed that the school canteen provides unhealthy snacks containing sweeteners, preservatives, and food coloring. Regular consumption of these snacks can increase the risk of non-communicable diseases such as early-onset diabetes mellitus. The purpose of this activity is to educate students, teachers, and canteen managers about healthy, halal, and thoyib snacks to raise awareness of the importance of choosing safe snacks and to protect students from health risks at an early age. Education was also provided to food vendors on the importance of maintaining food safety and nutrition. The methods used included socialization and education through lectures, Q&A sessions, and engaging communication media such as animated videos, educational games, and standing banners. The results showed strong support from stakeholders, including the school principal, teachers, canteen managers, students, and university students, which ensured the smooth implementation of the program. Prior coordination, both offline and online, helped clarify the roles of each party. Awareness of the importance of healthy, halal, and thoyib snacks increased, and there was a stronger commitment to creating a healthier school environment.